Urban Sketching - Guidelines for Designing a Sketching Interface for Early-Stage Urban Planning - Öhrn, Erik (My University, 2020)
While the process of urban planning uses sketching and analyses to a large degree, no guidelines exist for how to design an interface which combine the two. In this master’s thesis, 17 guidelines for how to design a sketching interface for early-stage urban planning are presented. These have been created by the means of literature review, in-depth interviews with urban planning experts, as well as the development three prototypes that have been evaluated by both human-computer interaction experts and urban planning experts.
Keywords: urban planning; sketching; sketch analysis; VirtualCity